2021
DOI: 10.3389/fneur.2021.639265
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Anti-NMDAR Encephalitis With Anti-MOG CNS Demyelination After Recurrent CNS Demyelination

Abstract: Introduction: Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis, a serious neurological autoimmune disorder caused by autoantibodies with diverse clinical manifestations, may simultaneously onset with antimyelin oligodendrocyte glycoprotein (MOG) demyelination after recurrent central nervous system (CNS) demyelination.Case Report: We present a case of anti-NMDAR encephalitis combining with anti-MOG CNS demyelination following recurrent CNS demyelination. A 38-year-old man admitted to hospital developed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The coexistence of anti-MOG and anti-NMDAR antibodies has also been increasingly reported in both adult and paediatric patients. [22][23][24][25][26] In a recent study, Hou et al 22 reported seven patients with anti-NMDAR encephalitis combined with anti-MOG antibodies. Two of their patients did not show any clinical features of anti-MOG-associated demyelination during the follow-up period, which is similar to our single case (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of anti-MOG and anti-NMDAR antibodies has also been increasingly reported in both adult and paediatric patients. [22][23][24][25][26] In a recent study, Hou et al 22 reported seven patients with anti-NMDAR encephalitis combined with anti-MOG antibodies. Two of their patients did not show any clinical features of anti-MOG-associated demyelination during the follow-up period, which is similar to our single case (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“… 3 This finding implies a difference in the immunopathogenic mechanisms involved in the development of each entity, such that AQP4-IgG + NMOSD is more attributable to a defect in immune tolerance, while MOGAD is more likely to be an aberrant autoimmune response to certain triggers, such as infection, vaccination, or malignancy. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The major finding of our study was that the most frequent autoimmune disorder that has been reported to co-exist with MOGAD is anti-NMDAR-EN, which is a similar finding to previous studies. 53 Some studies have referred to this co-occurrence as “overlapping syndrome of MOGAD and anti-NMDAR-EN, (MNOS).” 19 , 51 In our literature review, we captured a total of 200 patients who either met the diagnostic criteria for autoimmune encephalitis and were simultaneously seropositive for both anti-NMDAR-IgG, and MOG-IgG or who met the diagnostic criteria for each of MOG-associated encephalitis (MOGAD-EN) or anti-NMDAR-EN and was seropositive for the antibody associated with the other one, at the same time. 10 Given the rarity of both MOGAD and anti-NMDAR-EN, the co-occurrence of these two entities may happen in the context of an association or could be just a coincidence.…”
Section: Discussionmentioning
confidence: 99%